MUHAMMAD IQBAL AND THE IDEA OF DYNAMIC ISLAM - Sarbini Anim (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
This article explores Muhammad Iqbal's profound influence on the concept of Islamic dynamism in the early 20th century. Known as Allama Iqbal, he significantly shaped Pakistan's ideological foundations and advocated for a rejuvenated understanding of Islam in the context of modernity. The article delves into Iqbal's philosophical views on the dynamic nature of Islamic thought, emphasizing its adaptability to contemporary challenges. It examines his vision of a dynamic Islamic philosophy that balances tradition with progress, stressing the need for intellectual and spiritual revival. Additionally, the article explores Iqbal's ideas on integrating traditional Islamic values with advancements in science, philosophy, and social dynamics. It highlights his call for a unified Muslim community, transcending geographical and cultural boundaries, and discusses his impact on political discourse, advocating for the harmonious integration of Islamic principles into the socio-political fabric. In conclusion, the article aims to provide a comprehensive understanding of Iqbal's nuanced perspective, urging Muslims to embrace a dynamic approach for intellectual growth, societal development, and a unified Muslim identity in the contemporary world.